PENGUATAN HUMAN SECURITY MELALUI PEMBERDAYAAN PEREMPUAN DI DESA BRUJUL KECAMATAN JATEN KABUPATEN KARANGANYAR - Setyasih Harini Halifa Haqqi (Lembaga Penelitian dan Pengabdian Masyarakat, 2018)
Modern society is the result of joint relations between men and women. Nowadays, women’s subordination obstacle to women ‘s development and advancement. Women’s subordination as a kind of patriarchy system also deeper poverty. No progres of society without women activities. Empowering of women become a way to increase human security. The purpose is how to empower village women of Brujul, sub-district Jaten, Karanganyar regency. Increasing empowerment of village women is very important. It can develop and progress society in that village. There are three indicators of women empowerment: security, decision making and mobility. Method of this community service is meeting and discussion with the women of Brujul village. The result of this discussion that security of the women from Brujul still influenced by patriarchy system and lower education. Furthermore, the older married women had less power to increase their security. The younger married women with higher education have more power in decision making process of houshold and health. Higher education background can influence of women mobility. The women mobility also dependent upon how their family view women’s right. The result of this community service show that increasing knowledge about human right, human security and empowerment is very important for the women of Brujul village.Key words: women, empowerment, human security